Surplus suffering: the search for help when a child has mental‐health issues. Issue 2 (7th February 2012) - Clarke, Juanne N.
ABSTRACT: Social theorists have demonstrated the growth in dominance of two central discourses for understanding the ways that children's mental‐health issues are understood today – medicalization and intensive mothering . In this context, this paper reports on a qualitative interview‐based study of 16 mothers whose children had received a diagnosis with one or more mental‐health or developmental issues such as Tourette's, bipolar, anxiety, depression, autism or attention deficit hyperactivity disorder. It is based on the retrospective accounts of mothers given during interviews, from the time when they noticed what they thought to be unusual behaviours and decided to try to normalize and accommodate to their children's behaviours and then to the various steps they took to seek help. The paper begins with a description of the sorts of problems that mothers noticed. It then moves to the strategies mothers then took to cope, manage and socialize their children. When these failed, mothers sought professional assistance with understanding, remediation and/or a diagnosis for the child(ren). Mothers described uncertainty, confusion and contradictions as they unremittingly sought help. This process may be called surplus suffering . The relevance of the theoretical issues is then reconsidered along with the substantive and practical consequences of the findings.